1993
DOI: 10.1111/j.1476-5381.1993.tb13631.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calyculin A on tension and myosin phosphorylation in skinned smooth muscle of the rabbit mesenteric artery

Abstract: 1 Using P-escin and ionomycin-treated skinned smooth muscle strips of the rabbit mesenteric artery, the effects of calyculin A (CL-A, an inhibitor of type 1 and 2A phosphatases) on mechanical activities, phosphorylation of myosin light chain (MLC) and the relationship between the two were studied in Ca2+-free solution containing 4 mM EGTA and these effects were compared with those evoked by Ca2 .2 The threshold concentration of Ca2+ required to increase either tension or MLC-phosphorylation was 0.1 M and maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…In contrast, myocytes with tonic contractile patterns, such as hVM require prolonged contractions with relatively small changes in amplitude over time. Such speculation is supported by reports showing that pRLC corresponds linearly with tension development in hVM [27] and that ppRLC in hVM appears to be less important than pRLC [28][29][30]. These pathways were elucidated through the use of combinations of physiological agonists and pharmacological inhibitors.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, myocytes with tonic contractile patterns, such as hVM require prolonged contractions with relatively small changes in amplitude over time. Such speculation is supported by reports showing that pRLC corresponds linearly with tension development in hVM [27] and that ppRLC in hVM appears to be less important than pRLC [28][29][30]. These pathways were elucidated through the use of combinations of physiological agonists and pharmacological inhibitors.…”
Section: Discussionmentioning
confidence: 84%
“…It has been known that smooth muscle contracts even in the absence of Ca 2ϩ if protein phosphatase inhibitors such as okadaic acid (16,(42)(43)(44), calyculin A (45,46), tautomycin (16,47), or microcystin (16 -19) are added. Recently, Weber et al (19) reported that microcystin induced Ca 2ϩ -free contractions of Triton X-100-skinned rat caudal arterial smooth muscle and that during the Ca 2ϩ -free contraction, myosin regulatory light chain was phosphorylated at both Ser 19 and Thr 18 .…”
Section: Discussionmentioning
confidence: 99%
“…H-7 can inhibit cyclic nucleotide-dependent protein kinases in addition to protein kinase C (Hidaka et al, 1984), although the possible role of these enzymes in responses to 5-HT will require further study (see Sumner et al, 1992). It has also been suggested that H-7 directly inhibits myosin light chain kinase (Suzuki & Itoh, 1993), but the concentration of H-7 used in the present study did not inhibit contraction to Ca2+, so that the 5-HT-induced increase in Ca2+ sensitivity may well involve protein kinase C. Previous studies on the rabbit mesenteric artery have also shown that H-7 and another protein kinase C inhibitor, staurosporine can inhibit noradrenaline, endothelin and GTP-7-S-induced contractions at fixed [Ca2+]j, and that the protein kinase C activator phorbol 12,13-dibutyrate increased the Ca2+-sensitivity of the contractile filaments (Nishimura et al, 1991).…”
Section: Discussionmentioning
confidence: 99%